CITY BRANDING AND THE TOURIST GAZE: PENGEMBANGAN WISATA KOTA - Siregar, Afrila Mulyati Siregar; Suharyono, Suharyono; Kusumawati, Andriani (PROFIT: JURNAL ADMINISTRASI BISNIS, 2020)
The purpose of this study is to present the conceptual framework of city branding that combines it with the concept of tourist gaze as a tourist perspective which makes it a framework for attracting tourists, investors and new residents, especially in city tourism. This study explores the essence of city branding that is linked to urban tourism through the theory of "Tourist Gaze" by John Urry, then links with the city image, and the relationship between city imaging. Branding has symbolic value because branding is a strategy to provide places, cities, images, and cultural meanings. Branding shows the need for individuality and emotional connection with the environment in the context of globalization, thus providing depth and originality of the city or its distinctive character. .